Whispers From The Dead - Nixon, Joan Lowery (New York, 1989)
After making contact with the spirit world during a near-death experience, Sarah moves to Houston with her parents and receives otherworldly messages about a murder committed in her house.
"Laurel-leaf books."
Keywords: Supernatural; Fiction; Murder; Fiction; Mystery and detective stories